Reforma al art. 634 del Código de Trabajo, en cuanto al término para la declaración del abandono de las instancias o recursos, en los juicios individuales de trabajo - Rodríguez Vivar, Walter Fraygil (2015)
This research has allowed a scientific- legal study on the declaration of abandonment of resources and instances in individual trials work , for which he was raised as a general objective: To make a doctrinal , legal and empirical study of the legal regime regulating the labor process , and establish clearly whether the rights of workers to the term set for the declaration of abandonment of an action in the workplace are violated . The data obtained in this research work were obtained from the use of surveys and polls to professionals involved in the issue and doing their practice in this area. The legal background that served as diagnosis allowed us to confirm the existence of cases of alleged neglect of resources by the workers. These data have been processed and interpreted in a manner that constitute reliable sources that allow us to justify the need for a reform allowing same ,, to assert the rights of workers established in the Constitution and the Labor Code itself